Effect of Whey Protein Isolate and Soy Protein Isolate on Textural Properties and Syneresis of Frozen Traditional Chinese Hot Pot Egg Sausage Gels - Lin, Hong-Ting Victor; Huang, Luan-Hui; Tsai, Jenn-Shou; Sung, Wen-Chieh (Gels, 2024)
Egg sausages, an essential component of traditional Chinese hot pot cuisine, have specific storage requirements and are predominantly distributed through refrigerated channels. A significant consideration in the freezing of egg sausages pertains to syneresis and textural modifications that manifest in the protein gel structure upon thawing. This research investigated the efficacy of incorporating whey protein isolate, soy protein isolate (at concentrations of 0.5%, 1.0%, and 2.0%), and modified cassava starch (at concentrations of 1.0%, 2.0%, and 3.0%) to enhance the textural integrity and mitigate syneresis in frozen egg sausage gels. The research demonstrated that syneresis in frozen egg sausages could be significantly minimized from 9.01% to 1.16% through the incorporation of 3% modified cassava starch and 2% whey protein isolate, to 2.01% with 1.0% soy protein isolate, and to 3.05% with 1.0% whey protein isolate. Furthermore, the combination of modified cassava starch (3%) and whey protein isolate (2%) demonstrated enhanced textural characteristics in frozen egg sausages with 20% additional water content following a 15-day storage period. Notably, egg sausages formulated with 0.5% whey protein isolate exhibited superior sensory attributes, including springiness, texture, and overall acceptability, compared to other formulations. The incorporation of whey protein isolate yielded markedly improved sensory characteristics relative to soy protein isolate additions. The findings indicate that the incorporation of whey protein isolate (0.5–1.0%) in conjunction with modified cassava starch (3%) effectively improves textural properties while reducing syneresis in thawed egg sausages.